Pelatihan Bertani Hidroponik dengan Memanfaatkan Lahan Pekarangan untuk Meningkatkan Kreativitas dan Ekonomi - M Farid Nasrulloh; Muhammad Rozak; Afrina Hidayatul Arifah; Rohmatul Fitriani; Fitri Umardiyah; Anton Muhibuddin (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2022)
At first, farmers in Gabusbanaran Village who worked as farmers worked on rice, corn, and seasonal crops. Along with the times, and the condition of the soil that is getting less and less fertile, and the pests that continue to attack the farmers' rice fields, although efforts have been made to eradicate the pests, the pests that are continuously given pesticides become resistant. Facing such a thing, the service implementer wishes to increase human resources and use the existing land in order to realize the socio-economic independence of the Gabusbanaran Village community. Community service activities are carried out using participatory methods for the target group, in this case the PKK group, IPNU & IPPNU youth in Gabusbanaran Village and the surrounding community. Here, the service implementer acts as a facilitator and guide for the target group to jointly carry out the planned activities. The method used is through training, demonstrations of making plant cultivation through hydroponics. The conclusion of community service activities, with this hydroponic plant cultivation training, the people of Gabusbanaran Village are increasingly skilled and creative in making hydroponics.